Monitoring and assessment of azulejo panels decay: The 20th century façade azulejos from Manuel Rocha building - Pereira Sílvia R. M.; Mota Rogério; Roque Dora; Coutinho Mathilda L.; Menezes Marluci; Matias Luís; Henriques Maria João; Santos Silva António (MATEC Web of Conferences)
This study investigates the deterioration of the 20th-century azulejo façades of the Manuel Rocha Building in Lisbon. A multi-technique approach, including SEM-EDS, XRD, GPR, thermography, and hyperspectral imaging, was used to characterise materials and assess decay. Photogrammetry and digital image processing enabled mapping of pathologies and reconstruction of the decay chronology. Results indicate rapid degradation, with some panels reaching a critical state of degradation if no intervention is undertaken. The presence of alkali-silica gels suggests that alkali-silica reactions may be a key factor in glaze detachment. Findings highlight the urgency of conservation measures and the value of integrated monitoring strategies for heritage preservation.